Dilated cardiomyopathy arresponsive to treatment with taurine in feline with right congestive heart failure - Wajczyk, Talita; Teixeira, Leonardo; Fukuda, Aline; Wajczyk, Talita; Cristina Nehls Coutinho, Daina; de Abreu Pereira, Juliana (Pubvet, 2021)
In dilated cardiomyopathy the myocardium undergoes progressive degeneration, resulting in systolic failure. Dilatation of the cardiac chambers occurs concomitantly with the decrease in the thickness of the walls of the ventricles, which causes insufficiency of the atrioventricular valves, reduction of the contractility of the heart and an increase in the volume and final systolic diameter. In advanced stages, congestive heart failure is established, progressing to pulmonary congestion and pleural and pericardial effusion. A feline, mixed breed, neutered, weighing 4.9 kg, with no known history was seen at a veterinary clinic. He was alert, dyspnoic, with a significant increase in abdominal volume, normothermic, normal mucous membranes and with signs of pain in the abdominal region. Ultrasound showed an anechoic intra-abdominal fluid and dilated hepatic vascular architecture with preserved paths. On echocardiographic examination, there was insufficiency of major degree in the tricuspid valve, slight effusion in the pericardium without risk of cardiac tamponade and caudal vena cava with significant congestion with cardiogenic ascites and marked effusion in the pleural space. Analysis of cavity fluids indicated hemorrhagic effusion and modified transudate. The examinations showed a picture of dilated cardiomyopathy concomitant with right congestive heart failure. The report describes the established treatment, which allowed a survival of 48 days after the diagnosis of the pathology. The animal was responsive to supplementation with taurine.
Keywords: Dilated cardiomyopathy; feline; taurine